Design of Vibration and Noise Reduction System for Main Engine Installation on Ships: Perancangan Sistem Peredam Getaran dan Kebisingan pada Instalasi Mesin Utama Kapal - MAU, MARIO VILTORIUS MAU; MAU, MARIO VILTORIUS ROLANDSON (Blueprint Journal, 2025)
This study aims to design a vibration and noise dampening system and also dampen the sound that occurs in the ship's main engine, so that in the engine room, comfort and safety of work increase. The methods in this study include exploration at the literature level, measurement of actual vibration and noise values ​​recorded with a sound level meter and vibrimeter carving tool, and simulation design of dampening modeling using vibration isolators and acoustic dampening alloy materials. The test results also show that there is a significant reduction, in terms of noise and vibration levels, with the use of a mixture of dampening materials made of natural rubber and polyurethane, noise reducing bonds. This system performs its function as estimated to be able to reduce noise intensity by 18 dB and reduce vibration amplitude by 40%. The conclusion of this study is that the right dampening design can increase the level of acoustic comfort and increase the durability of spare parts or engine components.